(untitled) (International Journal of Advanced Research in Computer Science, 2017)
This new era is emerging towards the fast telecommunication technologies and this paper here is also explaining the newest technologies that are 4G & 5G and their evolution from the different projects working all over the world. Every forum uses different frequency band in GHz. Although here this paper will discuss the main issue of 5G technology and that is the power issue. FBMC as the main 5G technology aspirant and this also suffers from the problem of power which is being composed by the term PAPR ratio. PAPR reduction techniques like DSLM is used and the paper proposes this as the superior technique for improving the PAPR by deep scrutiny .